Effects of Graphic Organizer and Experiential Learning with Feedback on Students’ Achievement and Retention in Basic Science and Technology, Plateau State, Nigeria. - Edward, Bash Asabe; Kurumeh-, Seraphina M.C.; Samba, Regina Marita O. (NIU Journal of Humanities, 2020)
The study investigated the effects of graphic organizer and experiential learning with feedback on studentsâ€™ achievement and retention in Basic Science and Technology, Plateau State., Nigeria. Three research questions were answered and two hypotheses were tested at 0.05 level of significance. The study adopted a quasi- experimental design. Specifically, the separate sample pre-test post-test design. The population of the study comprised of 13,040 with a. sample of 325 junior secondary two students from six secondary schools in Zone B of Plateau State, Nigeria were selected using a multi-sampling technique, specifically the purposive sampling technique. The Basic Science and Technology Achievement Test (BSTAT) with reliability coefficient of 0.745 was used for data collection. The data collected was analyzed using Mean and Standard Deviation to answer the research questions While Analysis of Covariance (ANCOVA) was used in testing the hypotheses at 0.05 level of significance. The findings revealed that there were significant differences in both graphic organizer and experiential learning achievement with a mean score ( = 25.94, SD = 9.02) and group II had a mean score of (  = 29.01, SD = 10.08 before treatment. After treatment the results for experimental group II yielded a higher mean score (  = 61.54, SD = 9.64) than experimental group I ( = 50.24, SD = 14.62). The mean difference is high with 8.23. On the investigation on gender, there was also significant difference in the mean achievement of male and female, in favour of female. It was recommended among others that the two strategies can be used for teaching of Basic Science and Technology to enhance high achievement in Basic Science and Technology achievement and enhancement of retention in students. Furthermore, stake holders should organize seminars and workshops to train teachers on how to use graphic organizer and experiential learning with feedback for teaching. Keywords: Effect, Graphic organizer, Experiential learning, Basic Science and Technology, Gender, Retention.